Predictive value of atherogenic index of plasma and atherogenic index of plasma combined with low-density lipoprotein cholesterol for the risk of acute myocardial infarction - Chen, Min; Fang, Cao-yang; Guo, Jiong-chao; Pang, La-mei; Zhou, Yuan; Hong, Yu; Yang, Lin-fei; Zhang, Jing; Zhang, Ting; Zhou, Bing-feng; Hu, Guang-quan (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background and aims: Acute myocardial infarction (AMI) is a prevalent medical condition associated with significant morbidity and mortality rates. The principal underlying factor leading to myocardial infarction is atherosclerosis, with dyslipidemia being a key risk factor. Nonetheless, relying solely on a single lipid level is insufficient for accurately predicting the onset and progression of AMI. The present investigation aims to assess established clinical indicators in China, in an effort to identify practical, precise and effective tools for predicting AMI. Methods: The study enrolled 267 patients diagnosed with acute myocardial infarction as the experimental group, while the control group consisted of 73 hospitalized patients with normal coronary angiography. The investigators collected general clinical data and relevant laboratory test results and computed the Atherogenic Index of Plasma (AIP) for each participant. Using acute myocardial infarction status as the dependent variable and controlling for confounding factors such as smoking history, fasting plasma glucose (FPG), low-density lipoprotein cholesterol (LDL-C), blood pressure at admission, and diabetes history, the researchers conducted multivariate logistic regression analysis with AIP as an independent variable. Receiver operating characteristic (ROC) curves were employed to determine the predictive value of AIP and AIP combined with LDL-C for acute myocardial infarction. Result: The results of the multivariate logistic regression analysis indicated that the Atherogenic Index of Plasma (AIP) was an independent predictor of acute myocardial infarction. The optimal cut-off value for AIP to predict acute myocardial infarction was -0.06142, with a sensitivity of 81.3%, a specificity of 65.8%, and an area under the curve (AUC) of 0.801 (95%CI: 0.743-0.859, P<0.001). When AIP was combined with low-density lipoprotein cholesterol (LDL-C), the best cut-off value for predicting acute myocardial infarction was 0.756107, with a sensitivity of 79%, a specificity of 74%, and an AUC of 0.819 (95%CI: 0.759-0.879, P<0.001). Conclusions: The Atherogenic Index of Plasma (AIP) is considered as an autonomous determinant of risk for acute myocardial infarction (AMI). Utilizing the AIP index alone, as well as in conjunction with low-density lipoprotein cholesterol (LDL-C), can serve as effective predictors of AMI.